COLON SPECIFIC ROLE FOR SELENOPROTEIN P IN COLITIS AND COLITIS-ASSOCIATED CARCINOMA. (21st January 2021) - Short, Sarah; Pilat, Jennifer; Reddy, Vishruth; Haberman, Yael; Hendren, Jared; Washington, Mary; Hyams, Jeffrey; Denson, Lee; Rosen, Michael; Williams, Christopher
Abstract: Selenium (Se) is an essential trace element incorporated into selenoproteins (SEPs), which provide a broad scope of antioxidant functions. Se status inversely correlates with inflammatory bowel disease (IBD) severity, and animal models have shown that Se deficiency worsens colitis and colitis-associated cancer (CAC). One of the most highly expressed and functionally critical SEPs is Selenoprotein P (SEPP1/SELENOP). SELENOP serves two known roles: 1) distributing Se throughout the organism, and 2) acting as a lipid peroxidase. SELENOP is also markedly reduced in IBD. Global SELENOP reduction augmented experimental CAC. SELENOP is primarily produced in the liver for tissue distribution through the plasma; however, liver-specific SELENOP deletion failed to modify CAC, thus implicating epithelial SELENOP as a primary disease modifier. As the roles of intestinal epithelial SELENOP in colitis and CAC remain unknown, we investigated these roles using the Vil-CreERT2 driver to inducibly delete intestinal epithelial SELENOP in AOM/DSS inflammatory carcinogenesis models. First, Selenop deletion was confirmed in intestinal epithelial cells of tamoxifen-induced Vil-CreERT2; Selenopfl/fl mice (ΔIEC). Epithelial-specific SELENOP loss promoted tumor initiation, as evidenced by greater tumor multiplicity visible by colonoscopy in ΔIEC mice. Upon sacrifice, ΔIEC mice demonstrated increased colon tumor number and size. Additionally, ΔIEC colon tumors displayed greater apoptosis (cleaved caspase-3), DNA damage (pγH2AX), and dysplasia severity. Overall, these results are consistent with our model that epithelial SELENOP loss promotes tumor formation through increased intratumoral oxidative stress and resultant genomic instability. To further investigate SELENOP's contributions in pure epithelial cultures, we determined that both CACO2 cells and human colonoids produce SELENOP in a sodium selenite-dependent fashion; furthermore, polarized CACO2 cells preferentially secrete SELENOP basolaterally, suggesting a local extracellular role for SELENOP in the immediate colonic epithelial microenvironment. Also, SELENOP knockdown in human intestinal organoids derived from ulcerative colitis (UC) patients increased oxidative stress, increased sensitivity to H2O2 treatment, and reduced organoid growth, implicating SELENOP in modulating the epithelial ROS-protective response. RNA-seq analysis from the PROTECT cohort revealed reduced SELENOP expression in pediatric UC biopsies that inversely correlated with disease activity and S100A8 (calprotectin) levels. Lastly, SELENOP RNA in situ hybridization of adult UC/Crohn's Disease and CAC TMAs demonstrated decreased epithelial transcript in IBD and stage-dependent reductions in CAC. These data collectively indicate critical roles for SELENOP in epithelial and colonic microenvironment antioxidant defenses in IBD.